A comparative study of the legal liability of executives in LLC in the Czech Republic and some of other EU member states - Cvik, Eva Daniela; MacGregor Pelikánová, Radka (Univerzita Pardubice, 2016)
The limited liability company (LLC) appears to be among the most popular forms for business conduct for small and medium sized enterprises (SME) in the EU. Due to the extreme competitiveness and challenging global market, there is a strong external, as well as internal, pressure on the executives of LLCs from various angles. Their challenging situation is projected within the legal framework of the status and the function of executives, and in particular in the regime of their legal liability. It is highly instructive to compare the Czech regime to regimes in other EU member states while focussing on the liability issue. Interestingly, there is a big diversity in modes of addressing this liability and, consequently, the very same problem of the business judgment rule and the liability coverage is resolved in a different manner. Ultimately, the insurance approach v. professional advice approach shows how the shifting of the liability of executives of LLCs is done in various legal systems and testifies about underlying concepts and particularities of conducting business in EU member states.
Keywords: statutory authority; liability; executive service agreement; re-codification; limited liability company; K22; M12